Individualized Levels System and Systematic Stimulus Pairing to Reduce Multiply Controlled Aggression of a Child With Autism Spectrum Disorder. Issue 3 (May 2018) - Randall, Kayla R.; Lambert, Joseph M.; Matthews, Mary P.; Houchins-Juarez, Nealetta J.
Research has shown that physical aggression is common in individuals with autism spectrum disorder (ASD). Interventions for multiply controlled aggression may be complex and difficult to implement with fidelity. As a result, the probability of treatment efficacy for this class of behavior may suffer. We designed an individualized levels system to reduce the physical aggression of an 11-year-old female with ASD. We then employed a systematic stimulus pairing procedure to facilitate generalization. Results suggest individualized levels systems can suppress multiply controlled aggression and that systematic stimulus pairing is an effective way to transfer treatment effects from trained therapists to caregivers.